PERAN BUDAYA SEKOLAH TERHADAP KINERJA GURU PROFESIONAL PADA SEKOLAH MENENGAH ATAS KOTA TERNATE, PROVINSI MALUKU UTARA - Habsyi, Irsan; Habsyi, Faisal Y (Jurnal Pendidikan dan Ekonomi (JUPEK), 2023)
The aim of this research is to determine the role of school culture on the performance of professional teachers. The research method used is a qualitative method using interview techniques, documentation studies and observations in collecting data on ten teachers and ten principals at state high schools in the city of Ternate. The results of the research show that teachers in senior high schools in the city of Ternate are trying to improve school culture which leads to high quality professional teacher performance.